Duration of resuscitation and long-term outcome after in-hospital cardiac arrest: A nationwide observational study. (October 2022) - Yonis, Harman; Andersen, Mikkel Porsborg; Mills, Elisabeth Helen Anna; Winkel, Bo Gregers; Wissenberg, Mads; Køber, Lars; Gislason, Gunnar; Folke, Fredrik; Larsen, Jacob Moesgaard; Søgaard, Peter; Torp-Pedersen, Christian; Kragholm, Kristian Hay
Abstract: Background: Prior studies have investigated the association between duration of resuscitation and short-term outcomes following in-hospital cardiac arrest (IHCA). However, it remains unknown whether there is an association between duration of resuscitation and long-term survival and functional outcomes. Method: We linked data from the Danish in-hospital cardiac arrest registry with nationwide registries and identified 8, 727 patients between 2013 and 2019. Patients were stratified into four groups (A–D) according to quartiles of duration of resuscitation. Standardized average probability of outcomes was estimated using logistic regression. Results: Of 8, 727 patients, 53.1% ( n = 4, 604) achieved return of spontaneous circulation. Median age was 74 (1st–3rd quartile [Q1–Q3] 65–81 years) and 63.1% were men. Among all IHCA patients the standardized 30-day survival was 62.0% (95% CI 59.8–64.2%) for group A (<5 minutes), 32.7% (30.8–34.6%) for group B (5–11 minutes), 14.4% (12.9–15.9%) for group C (12–20 minutes) and 8.1% (7.0–9.1%) for group D (21 minutes or more). Similarly, 1-year survival was also highest for group A (50.4%; 48.2–52.6%) gradually decreasing to 6.6% (5.6–7.6%) in group D. Among 30-day survivors, survival without anoxic brain damage or nursing home admission within one-year post-arrest was highest for group A (80.4%; 78.2–82.6%), decreasing to 73.3% (70.0–76.6%) in group B, 67.2% (61.7–72.6%) in group C and 73.3% (66.9–79.7%) in group D. Conclusion: Shorter duration of resuscitation attempt during an IHCA is associated with higher 30-day and 1-year survival. Furthermore, we found that the majority of 30-day survivors were still alive 1-year post-arrest without anoxic brain damage or nursing home admission despite prolonged resuscitation.